The Impact of Vaping on Primary Spontaneous Pneumothorax Outcomes. Issue 4 (April 2023) - Shah, Mohsin; Bryant, Mary K.; Mody, Gita N.; Maine, Rebecca G.; Williams, Judson B.; Upham, Trevor C.
Introduction: Cigarette smoking is associated with primary spontaneous pneumothorax (PSP). Electronic cigarettes (E-cigarettes) are touted as a healthier alternative to cigarettes; however, the impact E-cigarette use has on PSP management is not known. The goal of this study was to determine if E-cigarette use is associated with inferior outcomes after PSP, compared to never smokers and cigarette smokers. Methods: We conducted a retrospective cohort study of patients in a large tertiary care hospital system in an urban area who presented with PSP from September 2015 through February 2019. Primary spontaneous pneumothorax patients were identified from the institutional Society of Thoracic Surgeon (STS) database. Patients with pneumothoraces from traumatic, iatrogenic, and secondary etiologies were excluded. Baseline clinical and demographic data and outcomes including intervention(s) required, length of stay, and recurrence were evaluated. Results: Identified were 71 patients with PSP. Seventeen (24%) had unverifiable smoking history. Of the remaining, 7 (13%) currently vaped, 27(50%) currently smoked cigarettes, and 20(37%) were never smokers. Mean age was 33 years; 80% male. All vapers required tube thoracostomy vs 74% of current smokers and 75% of never smokers. Vaping was associated with increased odds of recurrence compared to never smokers (OR 2.00, 95% CI 0.35, 11.44). Vapers had the shortest median time to recurrence after initial hospitalization (10 d[4, 18] v 20 d[5, 13] cigarette smokers v 27 d[13 275] never smokers, P < .001). Conclusion: Vaping may complicate PSP outcomes. As vaping use increases, especially among adolescents, it is imperative that the manner of tobacco use is documented and considered when caring for patients, especially those with pulmonary problems.